Communication Network of Women Vegetable Growers of Nainital District of Uttarakhand - Deepika Verma and Gyanendra Sharma, (Indian Journal of Extension Education, 2017)
Acommunication network consists of interconnected individuals who are linked by a patterned exchange of information.Its analysis identifies the communication structure in a system. Exchange of information and its diffusion takes placewithin a social system and the roles of actors such as people and organizations affect the diffusion of the innovationprocess. The present study was undertaken to delineate the communication network of women vegetable growers ofNainital district of Uttarakhand state. The study was conducted in six randomly selected villages of CommunityDevelopment Blocks namely, Haldwani, Ramnagar and Dhari in Nainital district during 2012-2014. The approach ofsociometry was applied to probe the key communicators in dissemination of vegetable related information. Therespondents were asked from whom they seek advice or suggestion in matters related to vegetable cultivation .Theirresponses were noted and key communicators were identified and diagrammatically depicted using target sociogramtechnique. Communication stars of each village were identified from the sample respondents. Results of the studyemphasized on capacity building programme for communication stars to promote vegetable cultivation.